The writing of places of memory in some novels of Africa and the West indies - (:unkn) unknown (My University, 2019)
This thesis aims at re-defining the French concept of« place of memory » as defined by Pierre Nora in the West Indian and African spaces through the relationship between literature and history. Indeed, slavery, colonisation and apartheid serve as a background to a wide range of representations of places of memory in West Indian and African literatures. This thesis is composed of three main sections. The first section provides some historical context that allows connecting Africa and Caribbean Islands. The second section scrutinizes the topographic aspect of the places of memory in various ways: toponymy, heterotopia, spaces of power and landscapes. The third section, which sheds light on the notion of figure of memory, focuses on the experiences of historical and fictional characters, which enable to define new kinds of heroism.To that extent, this study leads to think about the challenges of collective memory of people in a postcolonial background in which « memories war » spreads out.
Keywords: African Research